Analisis Kualitas Air Sumur Berdasarkan Parameter Fisika, Kimia Dan Mikrobiologi di Desa Purbayan Sukoharjo - Carollin Hasanah Esucho Putri; Henny Parida Hutapea (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  Water is one of the components of life that plays an important role in the survival of living things. In this study, well water quality is regulated in Permenkes No. 32 of 2017 concerning environmental health quality standards and water health requirements for sanitary hygienic purposes and public baths. This study aims to assess and provide information on the quality of well water in Purbayan Village, Sukoharjo against the requirements of water quality standards. This research uses descriptive and quantitative methods. The sampling point in the well that is close to the industry is called well A and the well that is far from the industry is well B. The results obtained in well A temperature 25.0°C, TDS 78.0 mg/L, pH 7.66, iron content 0.636 mg/L, manganese <0.02 mg/L, zinc 0.025 mg/L, nitrate 0.457 mg/L, nitrite 0.002 mg/L, sulfate 11.393 mg/L, chloride 31.12 mg/L, total hardness 146 mg/L, coliform total 2 Jml/100 ml and in well B temperature 25,0°C, TDS 81 mg/L, pH 7.18, iron content 0.0978 mg/L, zinc 0.031 mg/L, nitrite 0.002 mg/L, sulfate 61.081 mg/L, chloride 19.321 mg/L, total hardness 186 mg/L, coliform total 2 Jml/100 ml shows that all physical, chemical and microbiological parameters meet the requirements of water quality standards. The microbiological parameters of the fecal coli test in wells A and B did not meet the quality standard requirements with a result of 2 Jml/100ml.Abstrak: Air merupakan salah satu yang memiliki peranan penting dalam keberlangsungan makhluk hidup sehingga kualitas dari air sangat perlu di jaga. Tujuan Penelitian mengkaji dan memberikan informasi kualitas air sumur di Desa Purbayan Sukoharjo terhadap syarat baku mutu air bersih. Penelitian ini menggunakan metode deskriptif kuantitatif. Titik pengambilan sampel pada sumur yang dekat dengan industri disebut sumur A dan sumur yang jauh dari industri sumur B. Hasil yang diperoleh pada sumur A temperatur 25,0°C, TDS 78,0 mg/L, pH 7,66, kandungan besi 0,636 mg/L, mangan <0,02 mg/L, seng 0,025 mg/L, nitrat 0,457 mg/L, nitrit 0,002 mg/L, sulfat 11,393 mg/L, klorida 31,12 mg/L, kesadahan total 146 mg/L, total coliform 2 Jml/100 ml dan pada sumur B temperatur 25,0°C, TDS 81 mg/L, pH 7,18, kandungan besi 0,0978 mg/L, seng 0,031 mg/L, nitrit 0,002 mg/L, sulfat 61,081 mg/L, klorida 19,321 mg/L, kesadahan total 186 mg/L, total coliform 2 Jml/100 ml. Menunjukkan keseluruhan parameter fisika dan kimia memenuhi syarat baku mutu air. Parameter mikrobiologi uji koli tinja pada sumur A dan B tidak memenuhi syarat baku mutu dengan hasil masing- masing 2 Jml/100ml.